Maria Teresa Gracis, Il Don Chisciotte ritrovato. Reencontrar a Don Quijote (Altre Modernità, 2024)
Maria Teresa Gracis, Il Don Chischiotte ritrovato. Reencontrar a Don Quijote(Treviso, Antiga Edizioni, 2023, 182 pp. ISBN 978-888-435-407-5) di Marianna Montanaro